Accelerated cassava varietal turnover in Tanzania, a direct result of cassava seed system interventions - Msami, J.; Ndalahwa, M.; Nickas, J.; Arbogast, M.; Nkwabi, J.; Mwakyusa, N.; Mwenisongole, A.; Matondo, D.G.; Kumar, P.L.; Legg, J. (Frontiers Media, 2025)
Cassava is a vital food security crop grown in the tropics primarily for its starchy tuberous roots that play a significant role in calorie intake in Africa. The cassava seed system has been historically neglected resulting in the widespread propagation of poor quality and diseased planting materials (stems/cuttings). Recently there have been ongoing efforts to modernise cassava breeding and improve seed delivery in Tanzania which have resulted in the creation of a functional and commercially sustainable cassava seed system. This system comprises a decentralized network of seed producers in a hierarchy from early generation to community-based seed with different quality assurance requirements at each level. Seed entrepreneurs are registered on a ‘SeedTracker™' database where volumes of seed produced can be tracked for each variety. In this study, we analysed SeedTracker™ data and household survey data to determine the Weighted Average Varietal Age (WAVA) of improved cassava varieties in Tanzania. We used total seed (cuttings) produced as weights for WAVA estimations. Results showed changes in WAVA from 11.3 years in 2018, 13.6 years in 2019, 13.5 years in 2020, 10.6 years in 2021, 11.4 years in 2022 to 10.1 years in 2023. This suggests that there is an accelerating turnover rate of improved cassava varieties. The findings of this study are useful to cassava seed system actors such as policymakers, quality assurance agencies, breeders, and seed businesses. This study also serves as an indicator of the positive impacts being achieved through cassava seed system interventions in the country. Furthermore, it validates the adopted cassava seed system model and suggests that the model could be readily adapted to other crop systems where varieties are being routinely monitored.